EFFECT OF JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT ON INTENTION TO LEAVE - Munir, Miftahul; Sudrajad, Muhammad (jfpublisher, 2022)
Introduction. The current work situation is not in line with expectations desired (the emergence of dissatisfaction at work). Most companies sure ever colored with the phenomenon of employees who have the desire to move (intention to leave). The research aims to determine the effect of Job Satisfaction, OrganizationalCommitment and Job Stress partially or simultaneously on the intention to leave atNahdlatul Ulama Hospital in Tuban. Method. The research uses a quantitative causal and associative approach. The sample amounted to 92 people. Determination of the sample in this study using the method of saturated sampling. Gathering data using questionnaires and interviews, while the analysis of data using multiple linear regression analysis. Result & Analysis. Research at a significance level of 5% showed that: 1) t-test result on job satisfaction variable is -2.162 with a significance value of 0.033. It means job satisfaction has a negative and significant influence on the intention to leave. 2) t-test on the organizational commitment variable is -2.333 with a significance value of 0.022. It means organizational commitment has a negative and significant influence on the intention to leave. 3) t-test on the job stress variable is 2.241 with a significant value of 0.021. it means job stress has a positive and significant influence on the intention to leave. 4) Determination coefficient test (R2) for X1, X2 and X3 is 0.234, which means the intention to leave can be influenced by job satisfaction, organizational commitment, and job stress around 23.4%, then other factors around 76.6%. Discussion. there is no significant effect significant between organizational commitment variables on employee intention to leave Nahdlatul Ulama Hospital in Tuban, where it is known that organizational commitment has negative influence, which means a high level of organizational commitment will make the intention to leave decrease and vice versa if the commitment the organization in a company is low, the intention to leave the employee will be high. with response time.